Mitochondrial dysfunction in central nervous system white matter disorders. Issue 11 (28th May 2014) - Morató, Laia; Bertini, Enrico; Verrigni, Daniela; Ardissone, Anna; Ruiz, Montse; Ferrer, Isidre; Uziel, Graziella; Pujol, Aurora; Matute, Carlos; Stys, Peter K.
<x xml:space="preserve">Abstract</x> Defects of mitochondrial respiration and function had been proposed as a major culprit in the most common neurodegenerative diseases, including prototypic diseases of central nervous system (CNS) white matter such as multiple sclerosis. The importance of mitochondria for white matter is best exemplified in a group of defects of the mitochondria oxidative metabolism called mitochondria leukoencephalopathies or encephalomyopathies. These diseases are clinically and genetically heterogeneous, given the dual control of the respiratory chain by nuclear and mitochondrial DNA, which makes the precise diagnosis and classification challenging. Our understanding of disease pathogenesis is nowadays still limited. Here, we review current knowledge on pathogenesis and genetics, outlining diagnostic clues for the various forms of mitochondria disease. In particular, we underscore the value of magnetic resonance imaging (MRI) for the differential diagnosis of specific types of mitochondrial leukoencephalopathies, such as genetic defects on SDHFA1. The use of novel technologies for gene identification, such as whole‐exome sequencing studies, is expected to shed light on novel molecular etiologies, broadening prenatal diagnosis, disease understanding, and therapeutic options. Current treatments are mostly palliative, but very promising novel gene and pharmacologic therapies are emerging, which may also benefit a growing list of secondary mitochondriopathies, such as the peroxisomal disease adrenoleukodystrophy. GLIA 2014;62:1878–1894